Taṣawwurāt Ṭullāb Markaz al-Lugah tijāh Taṭwīr Mahārat al-Kalām ʿabra Ṭarīqat al-Munāqasyah al-Thaqāfiyyah fī Jāmiʿah al-Kuwayt - Ahmad Jaylani; Mualim Wijaya (KURAS Institute, 2026)
To address the limited exploration of cultural pedagogical models in authentic diverse settings, this study aims to describe the perceptions of students at the Markaz al-Lugah, Kuwait University, regarding the improvement of mahārah kalām (speaking skills) through the cultural discussion method. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group model involving 56 students learning Arabic as a foreign language. Data were collected through an oral test constructed based on indicators of speaking fluency, accuracy of vocabulary and structure, clarity of pronunciation, confidence in speaking, and the ability to convey ideas communicatively. The research instrument was tested for validity and reliability, and the data were subsequently analyzed using normality tests, homogeneity tests, and a t-test. The results indicate that all instrument items were valid and reliable, making them appropriate for measuring speaking ability. Furthermore, the pretest and posttest data were normally distributed and exhibited homogeneous variance. The results of the Independent Samples t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the group using the cultural discussion method and the group using conventional learning methods. These findings, complemented by observational data, demonstrate that the cultural discussion method is effective in improving students’ speaking skills, particularly in terms of speaking confidence, fluency, vocabulary mastery, and the ability to express opinions. The multicultural environment also serves as a supporting factor, as it encourages students to use Arabic in real, interactive, and meaningful contexts. Therefore, the cultural discussion method can be considered a viable alternative for communicative and contextual Arabic language instruction.